Nanocomposites with functionalised polysaccharide nanocrystals through aqueous free radical polymerisation promoted by ozonolysis. (1st January 2016) - Espino-Pérez, E.; Gilbert, Robert G.; Domenek, S.; Brochier-Salon, M.C.; Belgacem, M.N.; Bras, J.
Highlights: Starch and cellulose nanocrystals were functionalised with polystyrene. The grafting was initiated by ozone. SNC functionalisation was six times more efficient than that of CNC. Grafting with polystyrene improved thermal stability of polysaccharide nanocrystals. Water barrier properties of polylactide nanocomposites improved by 90%. Abstract: Cellulose nanocrystals (CNC) and starch nanocrystals (SNC) were grafted by ozone-initiated free-radical polymerisation of styrene in a heterogeneous medium. Surface functionalisation was confirmed by infrared spectroscopy, contact angle measurements, and thermogravimetric and elemental analysis. X-ray diffraction and scanning electron microscopy showed that there was no significant change in the morphology or crystallinity of the nanoparticles following ozonolysis. The grafting efficiency, quantified by 13 C NMR, was greater for SNC, with a styrene/anhydroglucose ratio of 1.56 compared to 0.25 for CNC. The thermal stability improved by 100 °C. The contact angles were 97° and 78° following the SNC and CNC grafting, respectively, demonstrating the efficiency of the grafting in changing the surface properties even at low levels of surface substitution. The grafting increased the compatibility with the polylactide, and produced nanocomposites with improved water vapour barrier properties. Ozone-mediated grafting is thus a promising approach for surface functionalisation of polysaccharide nanocrystals.